ANALISIS ASPEK KEPERILAKUAN PADA PENERAPAN SISTEM AKUNTANSI PERSEDIAAN DI CV. SENYUM MEDIA - Berlinetta Setia Wandhana; Muhammad Firdaus; Nanda Widaninggar (JAKUMA : JURNAL AKUNTANSI DAN MANAJEMEN KEUANGAN, 2021)
This study aims to analyze the Behavioral Aspects of CV. Senyum Media The object of this research is Senyum Media Jl. Kalimantan, Senyum Media Jl. Trunojoyo, Senyum Media Jl.Ambulu. The population in this study were employees who worked on CV. Senyum Media. This study uses a saturation sample. The analytical tools in this study used Instrument Tests (Validity Test and Reliability Test), Classical Assumption Test (Normality Test, Multicollinearity Test, Heteroskadestisity Test), and Multiple Linear Regression Analysis (Coefficient of Determination, Simultaneous Test Test (F test) and Partial Test ( t test).The results showed that Attitude, Motivation, Emotion, Perception, Learning, and Personality had a positive effect on the Inventory Accounting System.This indicates that if Attitude, Motivation, Emotion, Perception, Learning, and Personality greatly support the performance of the Inventory Accounting System. to work optimally.